In-plane cyclic testing of full-scale reinforced concrete frames with innovative isolated infill walls strengthened by highly ductile concrete. (1st October 2022) - Lyu, Hao; Deng, Mingke; Han, Yagang; Ma, Fudong; Zhang, Yangxi
Abstract: Conventional infilled frames exhibit weak seismic performance in high-intensity zones owing to the strong infill-frame interaction and vulnerability of the infill masonry. In this study, an innovative infill frame system with isolated infill walls retrofitted with highly ductile concrete (HDC) layers is proposed with the aim of minimizing the infill–column interaction and improving the lateral strength and deformation of masonry-infilled frames. Four full-scale specimens, including one bare frame, one conventional infilled frame, one conventional infilled frame retrofitted with HDC layers, and one isolated infilled frame retrofitted with an HDC layer, were tested under in-plane cyclic loading. The results indicated that the proposed isolated infill solution could effectively minimize the interaction between the isolated infill and columns. The observed damage on the isolated infill wall was minimal, whereas the damage to the columns was nearly identical to that of the bare frame. The isolated infill frame exhibited a higher lateral strength, deformation, and energy dissipation than the conventional infilled frame. Additionally, the proposed analytical model is highly consistent with the experimental results and can be used in design-oriented equations for innovative isolated infill frames. Highlights: Full-scale reinforced concrete frames with innovative isolated infill walls were subjected to reverse cyclic tests. The damage of the isolated infill wall is negligible. Isolated infill frames exhibited significantly larger strength, deformation and energy dissipation than conventional infill frames. Calculation formulas are proposed to estimate the bearing capacity of isolated infill frames at different infill–column contact stages.